Genetic engineering: an efficient approach to mitigating biotic and abiotic stresses in sugarcane cultivation. (31st December 2022) - Verma, Krishan K.; Song, Xiu-Peng; Budeguer, Florencia; Nikpay, Amin; Enrique, Ramon; Singh, Munna; Zhang, Bao-Qing; Wu, Jian-Ming; Li, Yang-Rui
ABSTRACT: Abiotic stresses are the foremost limiting factors for crop productivity. Crop plants need to cope with adverse external pressure caused by various environmental conditions with their intrinsic biological mechanisms to keep their growth, development, and productivity. Climate-resilient, high-yielding crops need to be developed to maintain sustainable food supply. Over the last decade, understanding of the genetic complexity of agronomic traits in sugarcane has prompted the integrated application of genetic engineering to address specific biological questions. Genes for adaptation to environmental stress and yield enhancement traits are being determined and introgressed to develop elite sugarcane cultivars with improved characteristics through genetic engineering approaches. Here, we discuss the advancement to provide a reference for future sugarcane ( Saccharum spp.) genetic engineering.